Literature Review of Suram (Fever) in Siddha Medicine - Prasad, V.M.; Thayalini, T. (Journal of research in Traditional Medicine, 2018)
Background: Siddha Medicine is one of the Indigenous medical systems, which mentions about 4448 diseases affecting humans. Suram (fever) is considered as one of the diseases in Siddha Medicine whereas Western Medicine considers it as a sign and symptom of many diseases. Aim: The present literary review on Suram is aimed at incorporating all the relevant informations pertaining to understanding the synonyms, causes, pathology and types which have been mentioned in various Siddha literatures in scattered form. Materials & Methods: Literatures pertaining to Suram were reviewed from library of Unit of Siddha Medicine, University of Jaffna and main library of Jaffna municipal council. Thirteen books were identified and collected for this study. Observations: Out of 13 literatures, 7 (53.84 %) have mentioned about the causes of Suram. All 13 literatures have mentioned the types of Suram which are categorized based on Doshas. 45 causes are identified and categorized based on the Tridoshas (Vatha, Pitha and Kapha) through unhealthy diet and habits. Among the 182 types of Suram identified, 64 types (35%) fall under the category of mixed which are categorized based on the affected Doshas, Dhatus and clinical features. Vata and Vata Kapha Suram are mentioned in 77% of literature and 71% have considered the cause as vitiation of Vathadosha. Conclusion: A total of 182 types of Suram, due to Vatha and Vathakapha as the main cause has been mentioned in 77% of literature.The literary survey reveals, unhealthy food and habits (71%) as the main cause for Vatha and Vathakapha Suram.
Keywords: Literature review